Views of the Islands: The Geographical Perception of the Balearic Islands Among Graduate Students in Primary Education - Jaume Binimelis Sebastián; Antoni Ordinas Garau; Maurici Ruiz Pérez (Island Studies Journal, 2023)
Geographic literacy is a field of research with a great tradition. This area was first developed in the British and North American academic circles in the 1980s and 1990s, and research has continued until the present day. The analysis of perception and knowledge of geography has focused on the enclaves (toponyms) mentioned in the mental maps (place location knowledge) prepared by university undergraduate students of the primary education teaching major. However, this focus is also on an approach where few studies have been made, yet it has been facilitated by the incorporation of modern geographic information technologies. The authors test a methodology for surface area and perimeter size analysis on the mental maps of the Balearic Islands made by future teachers, comparing their distortions in relation to the real model. After analyzing the results, the most notable common pattern describing the insular students’ perception of the isles is ethnocentrism, which undoubtedly has important implications in the field of geographic education.